AlCoCrFeNi-NiTi high entropy alloy composites: Microstructure and wear performance. (August 2022) - Ghanbariha, M.; Farvizi, M.; Ebadzadeh, T.; Samiyan, A. Alizadeh; Kim, H.S.
Abstract: In the current research, AlCoCrFeNi–x wt% NiTi (x = 0, 5, and 10) high entropy alloy (HEA) composites were prepared using a combination of mechanical alloying and spark plasma sintering methods. Microstructural studies showed that the introduction of 5 wt% NiTi slightly changed the BCC and FCC fractions of the HEA matrix. However, in the HEA-10NiTi sample, which exhibited increase in the interfacial regions and acceleration of interdiffusion between elements, the (Ni, Al)-rich BCC phase fraction was considerably reduced. According to nano-indentation tests, the NiTi and BCC phases possess higher hardness-to-elastic modulus values that confirm the positive effect of these two phases on tribological behavior. Among the prepared specimens, HEA-5NiTi had the lowest wear rate (0.71 ± 0.01 mm 3 /N· m). This is attributable to the higher BCC phase fraction and reinforcing effect of the NiTi particles. Graphical Abstract: ga1